What would you like to do?
Why does a positive times a negative produces a negative?
Because when there is a positive and a negative in the same problem, it gives you a negative. An easy way to solve problems like that is if there is an odd number of negative signs, then your answer is going to be negative. If there is an even number of negative signs, then your answer is going to be positive. (no matter if there is a positive sign in a math problem).
4 people found this useful
Was this answer useful?
Thanks for the feedback!
There are a lot of long examples that help to visualize why a negative times a negative is a positive, but this is just going to be an algebraic proof. Let x = a*b + (…-a)*b + (-a)*(-b) If we factor out the (-a) for the second part of the equation, we are left with: x = a*b + (-a)*(b+(-b)) b+(-b) = 0, so the resulting equation is: x = a*b + (-a)*0 Any number times zero is zero, so: x = a*b Next, we go back to the original equation, and factor our the "b" from the first part, leaving: x = (a+(-a))*b + (-a)*(-b) a+(-a) = 0, so: x = 0*b + (-a)*(-b) 0*b = 0, so: x = (-a)*(-b) Now we see that x equals both a*b and (-a)*(-b), meaning: a*b = (-a)*(-b) So the product of 2 negative numbers must be equal the the product of their positive counterparts, i.e., a positive result.
Here is a proof. Let a and b be any two real numbers. Consider the number x defined as x = ab + (-a)(b) + (-a)(-b). We can write this out differently as x = ab + (-a)[ (b…) + (-b) ] Then, by factoring out -a , we find that x= ab + (-a)(0) = ab + 0 = ab. Also, x = [ a + (-a) ]b + (-a)(-b) And by factoring out b, we find that x=0 * b + (-a)(-b) = 0 + (-a)(-b) = (-a)(-b). Therefore x = ab and x = (-a)(-b) Then, by the transitivity of equality, we have ab = (-a)(-b).
Number Line Imagine a number line on which you walk. Multiplying x * y is taking x steps, each of size y. Negative steps require you to face the negative end of the line befo…re you start walking, and negative step sizes indicate they should go backwards (i.e., heel first). So, (-x) * (-y) means to stand on zero, face in the negative direction, and then take x backward steps, each of size y. A Proof Let a and b be any two real numbers. Consider the number x defined by x = ab + (-a)(b) + (-a)(-b). We can write x = ab + (-a)[ (b) + (-b) ] (factor out -a) = ab + (-a)(0) = ab + 0 = ab. Also, x = [ a + (-a) ]b + (-a)(-b) (factor out b) = 0 * b + (-a)(-b) = 0 + (-a)(-b) = (-a)(-b). So we have x = ab and x = (-a)(-b) Hence, by the transitivity of equality, we have ab = (-a)(-b). Because the opposite of a negative is a positive.
It is a rule in math!
ITS NOT! example, -2 + -4 = -6 not a negative! Never Never Never Jonah!! hi. actually, if you notice, the person above says tht -2+(-4)=-6. -6 is a sum, NOT a product. … as an answer to your question, the negatives cancel each other out and leave the number all by itself. i think that's it. -2 + -4 is not a CORRECT sum. you need to take out the positive sign when you have a positive and negative next to eachoter and complete the sum as it is -2-4=-6
the thing is that when there are two negatives you need to cross out those which will give positive times positive equals positive. this is the rule that you need to learn it.… negative*negative=positive positive*positive=positive negative*positive=negative The same thing for devision
A positive number times another positive number will give you a positive answer. If you multiply two negative numbers together, you will also have a positive answer. The only …way to get a negative answer is if you multiply a positive by a negative.
Negative times negative is always a positive.
Think of it like this: The product of a negative number times a number (call it B), will be the opposite sign of the sign of number B.The product of a positive number times a… number B, will have the same sign as the sign of number B.
No - it results in a negative number.
A+O X A-O Would have to be the genotype to yield 1/4 probability of any type O, as O is recessive and only expresses in homozygous condition.